Osteologic topography of the trochlear spine and fovea as landmarks to locate the superior oblique trochlea - Aglianó, Margherita; Franci, Daniela; Volpi, Nila; Orsini, Davide; Messina, Maddalena; Lorenzoni, Paola (Italian Journal of Anatomy and Embryology, 2019)
The position of the superior oblique tendon, attached to the orbital roof by a cartilaginous trochlea, is marked by osteologic landmarks like the trochlear spine and/or fovea, approximately located at the superomedial angle of the orbit. Aim of the study is to place the trochlea within the orbit with a series of measurements to give the surgeon detailed references of the trochlea location. For this purpose, we undertook the study of a collection of dry skulls of known sex and age to investigate bony landmarks. Measurements were taken to assess the position of the trochlear spine/fovea on a frontal plane employing a system of vertical and horizontal lines passing through known bony reference points. Measurements were also recorded between the trochlear spine/fovea and the orbital opening on one side and the anterior rim of the optic canal on the other side. The distances of the trochlear spine/fovea from the lines passing along the supraorbital notch and the frontozygomatic suture were respectively 8.5 ± 2.3 mm and 5.7 ± 1.5 mm. The distances of the trochlear fovea/spine from the anterior orbital opening and from the anterior rim of the optic foramen were respectively 4.2 ± 0.11 and 37.5 ± 3.1 mm. Only the distance from the optic canal showed sex-related differences. In conclusion, to avoid unwanted injuries of the trochlea of the superior oblique in surgery of the superomedial angle of the orbit, the surgeon should be aware of its precise position.